2013
DOI: 10.1371/journal.pone.0076299
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Mediates Persistent Epileptiform Activity In Vitro and In Vivo

Abstract: Epilepsy is a chronic brain disorder involving recurring seizures often precipitated by an earlier neuronal insult. The mechanisms that link the transient neuronal insult to the lasting state of epilepsy are unknown. Here we tested the possible role of DNA methylation in mediating long-term induction of epileptiform activity by transient kainic acid exposure using in vitro and in vivo rodent models. We analyzed changes in the gria2 gene, which encodes for the GluA2 subunit of the ionotropic glutamate, alpha-am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 56 publications
2
31
0
Order By: Relevance
“…It has been shown that mouse hippocampal slices treated with 2 h of KA exposure exhibit hypermethylation of the gria2 gene, and this effect persisted one week after the removal of the drug. RG108 was able to completely block the bursting activity and the persistent hypermethylation induced by KA [9]. In our study, the inhibition of increased methylation started on the 1st day after acute epileptic seizures, and this inhibition was significant by the 10th day when compared to the SE group.…”
Section: Discussionsupporting
confidence: 53%
“…It has been shown that mouse hippocampal slices treated with 2 h of KA exposure exhibit hypermethylation of the gria2 gene, and this effect persisted one week after the removal of the drug. RG108 was able to completely block the bursting activity and the persistent hypermethylation induced by KA [9]. In our study, the inhibition of increased methylation started on the 1st day after acute epileptic seizures, and this inhibition was significant by the 10th day when compared to the SE group.…”
Section: Discussionsupporting
confidence: 53%
“…Third, several lines of evidence support the conclusion that epigenetic factors and mechanisms are functionally deregulated in epilepsy, including analyses performed utilizing human specimens as well as many different animal models (Crowe et al, 2011; Huang et al, 2012; Hwang et al, 2013; Kobow and Blumcke, 2012; Kobow et al, 2009; Kobow et al, 2013; Machnes et al, 2013; Miller-Delaney et al, 2012; Park et al, 2014; Ryley Parrish et al, 2013; Sng et al, 2006; Taniura et al, 2006; Tsankova et al, 2004; Williams-Karnesky et al, 2013; Zhu et al, 2012). One of the most persuasive studies found that, in a rat model of TLE, increased levels of DNA methylation in the hippocampus are associated with epileptogenesis and that adenosine, an endogenous anticonvulsant and anti-epileptogenic factor, exerts these effects via inhibition of DNA methylation (Williams-Karnesky et al, 2013).…”
Section: Epigenetic Mechanisms and Epilepsymentioning
confidence: 92%
“…DNMTs also play a key role in the development of epilepsy as evidenced by studies of DNMT inhibitors. Inhibiting DNA methylation via DNMT inhibitor RG108 resulted in Gria2 upregulation and blocked the seizure inducing effects of kainic acid in the hippocampus (Machnes et al, 2013). …”
Section: Targeting Dna Methyl Transferases and Demethylasesmentioning
confidence: 99%